PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP LOYALITAS YANG DIMEDIASI OLEH KEPUASAN PELANGGAN (Studi pada Pengguna Jasa Kantor Pos Semarang) - Merlin Nur Pratiwi, 15.05.51.0221; Maskur, Ali (Students' Journal of Economic and Management, 2019)
This study aims to analyze the effect of service quality and customer value on loyalty that is mediated by customer satisfaction in post office users of Semarang. This research was conducted at the Post Office in Semarang. The population in this study is all customers who use services at the Post Office in Semarang. The sampling technique in this study uses non probability sampling with purposive sampling data collection method with a sample of 100 respondents. The primary data collection method uses questionnaire and interview methods. The data analysis technique used was the instrument test (validity and reliability test), multiple linear regression, and model test (f test and coefficient of determination), hypothesis testing, and mediation test. The results showed that: Service quality has a positive and significant effect on customer satisfaction. Customer value has a positive and significant effect on customer satisfaction. Service quality has a positive and significant effect on customer loyalty. Customer value has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty. The mediation test results in this study indicate that customer satisfaction does not mediate the effect of service quality on customer loyalty and value on loyalty.